In vitro antimicrobial and antibiofilm screening of eighteen Iranian medicinal plants - Maryam Hamidi; Ali Mohaghegh Toosi; Behjat Javadi; Javad Asili; Vahid Soheili; Abolfazl Shakeri (BMC, 2024)
Abstract Background Natural products are one of the best candidates for controlling drug-resistant pathogens, the advantages of which include low production costs and low side effects. In this study, as potential antimicrobials, the anti-bacterial and antibiofilm activities of several Iranian native medicinal plants were screened. Methods The antibacterial/antifungal and anti-biofilm activities of 18 medicinal plants including Reseda lutea L., Nepeta sintenisii Bunge., Stachys turcomanica Trautv., Stachys lavandulifolia Vahl, Diarthron antoninae (Pobed.) Kit Tan., Ziziphora clinopodioides Lam., Euphorbia kopetdaghi Prokh, Euphorbia serpens Kunth., Hymenocrater calycinus Benth., Scutellaria pinnatifida A.Ham., Viola tricolor L., Hypericum helianthemoides (Spach) Boiss., Hypericum scabrum L., Convolvulus lineatus L., Scabiosa rotata M.Bieb Greuter & Burdet, Delphinium semibarbatum Bien. Ex Boiss., Glycyrrhiza triphylla Fisch. & C.A.Mey., and Ziziphus jujuba Mill., against two Gram-positive bacteria, Staphylococcus aureus, Bacillus cereus, as well as two Gram-negative bacteria, Pseudomonas aeruginosa, Escherichia coli; and Candida albicans as a fungal strain, were evaluated. The minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC) values of the extracts against tested microorganisms were reported and we investigated their effect on the biofilm inhibition of Pseudomonas aeruginosa PAO1, Staphylococcus epidermis, Staphylococcus aureus and Streptococcus mutans. In addition, the effect of the extracts on the eradication of the biofilms of these bacteria was evaluated. Results In this study, H. scabrum was found to exhibit potentially significant activity against Gram-positive bacteria with the MIC range of 6.25-25 µg/mL. This extract also showed a significant effect on inhibiting the biofilm of S. aureus, S. mutans, and S. epidermidis and eradicating the biofilm of S. epidermidis DSMZ 3270. In addition, Hymenocrater calycinus root extract had moderate antibacterial activity against B. cereus with the MIC and MBC 62.5 µg/mL, respectively. Conclusions The results of this study showed that the root extracts of two plants, Hypericum scabrum and Hymenocrater calycinus, had antimicrobial and anti-biofilm effects. Based on the observed anti-biofilm effects, these two plants may be considered in future studies to find responsible antimicrobial compounds.